A neural model of empathic states in attachment-based psychotherapy - Cittern,D; Edalat,A (Computational Psychiatry, 2017)
We build on a neuroanatomical model of how empathic states can motivatecaregiving behaviour, via empathy circuit-driven activation of regions in thehypothalamus and amygdala which in turn stimulate a mesolimbic-ventral pal-lidum pathway, by integrating findings related to the perception of pain in selfand others. Based on this we propose a network to capture states of personaldistress and empathic concern, which are particularly relevant for psychothera-pists conducting attachment-based interventions. This model is then extendedfor the case of Self-Attachment therapy in which conceptualised components ofthe self serve as both the source of and target for empathic resonance, and weconsider how states of empathic concern involving an other that is perceived asbeing closely related to the self might enhance the motivation for self-directedbonding. We simulate our model computationally, and discuss the interplaybetween the bonding and empathy protocols of the therapy.